Lectotypifications of 15 names of Chinese taxa in three families - Duan, Yifan; Yang, Xin-Xin; Li, Yong-Fu; Shi, Ji-Sen; Wang, Xian-Rong (Phytotaxa, 2016)
The Nanjing Forestry University Herbarium (Nanjing, Jiangsu), coded as NF in the Index Herbarium (Thiers 2016), is one of the most important herbarium in Eastern China, especially for its collections in woody plants. While studying the type specimens housed at NF, the types of 15 names of Chinese taxa in three families were found to be represented by gatherings with two or more specimens, that can be regarded as syntypes (Arts. 9.5, 40.2 Note 1 of the ICN, McNeill et al., 2012). Lectotypes for these names were here designated according to Arts. 8.1, 8.2, 9.2 of the ICN (McNeill et al. 2012).